Reliability of categorical loudness scaling in the electrical domain. - Theelen - van den Hoek, Femke L.; Boymans, Monique; Stainsby, Thomas; Dreschler, Wouter A. (International Journal of Audiology, 2014)
Objective: In categorical loudness scaling (CLS), subjects rate the perceived loudness on a categorical scale with alternatives. ISO 16832 describes an internationally standardized CLS procedure for the acoustical domain. This study focuses on the reproducibility of CLS following the recommendations of ISO 16832 using electrical stimuli presented to cochlear implant (CI) users. Design: Repeated CLS measurements were done using single-electrode stimuli at four electrode positions. Loudness growth functions (LGFs) described loudness as a function of level (μA). LGF shapes were characterized with an exponential b parameter. The reproducibility of the b parameter and inter-session intra-subject differences in percentage dynamic range (DR) between 'Very Soft' and 'Loud - Very Loud' levels were analysed. Study sample: Ten CI users. Results: Inter-session differences did not significantly differ between loudness categories or electrode positions. Across loudness categories the standard deviation of inter-session differences equalled 7.2%DR. The reproducibility of LGF shapes was moderate (r = 0.63). The LGFs of 43% of the measured electrodes significantly deviated from linear (nonzero b parameter). Conclusions: The reproducibility was comparable to the reproducibility for acoustical stimulation in normal-hearing and hearing-impaired listeners. CLS data for electrical stimuli are preferably fitted with a model that is flexible in describing LGF shapes.